(untitled) (Voice: A Biannual & Bilingual Journal, 2023)
Carbon stock in plant bodies is the significantly longer period reservoir for the atmospheric CO2 that causes adverse impacts on living and non-living climatic and environmental factors while increasing its proportional concentration in air. The present study aimed to estimate the carbon stock in trees of Mahendra Multiple Campus territory. The study was carried out by purposive sampling method, where altogether ten plots were laid of size 8.92m radii and measured diameter at breast height (DBH) (1.3m) and angle of inclination was taken from 5m horizontal distance from the tree pole. The calculation was made following the equation given by Chave et al., 2005 for wet forests. In total 17 species of trees were reported with the dominant species Dalbergia sissoo followed by Corymbia citriodora based on DBH and population density. The total carbon stored by trees inside the territory of MMC, Nepalgunj was 76.44 tons per hectare which is approximately 1/3rd of the world’s tropical forest average carbon stock. It implies the importance of trees outside the forest in carbon sequestration and balancing carbon emissions. Further estimation of carbon dioxide emitted from the territory, by different carbon emitters inside the area is recommended.